HUBUNGAN MINAT DENGAN PRESTASI BELAJAR BAHASA ARAB SISWA DI SEKOLAH MENENGAH PERTAMA LABSHOOL UPI BANDUNG - Fauziah, Hana (2016)
Interest is one of the influence factors of learning achievement. The purpose of this research is to know the existence of positive relation and significance between interest in learning and student achievement in learning Arabic language in grade VIIIthE in SMP Labschool UPI Bandung at Academic Year 2015/2016. This research use method of correlational research. Population in this research is all students in grade VIIIthE. Sample collection technique in this research use total sample technique. Data collection performed with questionnaire and documentation of test scores. For analysing the data, this research use product moment correlation. Pre-test analysis performed with normality test and hypothesis. Analysis technique and pre-test analysis performed with software SPSS 20 for windows. The result research indicates there's positive relation and significance between interest in learning and student achievement in learning Arabic language in grade VIIIthE in SMP Labschool UPI Bandung. The result research also show that students as this research object, 11,53% of them have lower interest in learning, 80,76% of them have middle interest in learning, 7,7% of them have higher interest in learning. From the data we know that 19,23% students grade VIIIthE in SMP Labschool have lower learning achievement Arabic language, 53,85% of them have middle learning achievement Arabic language, and 26,92% of them have higher learning achievement Arabic language. Based on data analysis, show that rcount (0,53) > rtable (0,388) with level error in the amount of 0,05 and N=26 ,its mean there's a significance relationship between interest in learning Arabic language and learning achievement with correlation score in the amount of 0,53. While koeficiency determination is 28,09%.;---Penelitian ini bertujuan untuk mengetahui ada atau tidaknya hubungan yang positif dan signifikan antara minat belajar dengan prestasi belajar bahasa Arab siswa kelas VIIIE SMP Labschool UPI Bandung, tahun ajaran 2015/2016. Metode penelitian yang digunakan adalah metode penelitian korelasional. Populasi pada penelitian ini adalah seluruh siswa kelas VIIIE di SMP Labschool UPI Bandung. Teknik pengambilan sampel penelitian menggunakan teknik sampel total. Pengumpulan data dilakukan dengan angket dan dokumentasi nilai ujian kenaikan kelas. Teknik analisis data yang digunakan adalah dengan rumus korelasi product moment. Uji prasyaratanalisis berupa uji normalitas dan hipotesis. Teknik analisis dan uji prasyaratanalisis menggunakan software SPSS 20 for windows. Hasil penelitian menunjukkan bahwa ada hubungan yang positif dansignifikan antara minat belajar dengan prestasi belajar bahasa Arab siswa kelas VIIIE SMP Labschool UPI Bandung. Hasil penelitian menunjukkan bahwa siswa yang menjadi obyek penelitian ini, 11,53% diantaranya memiliki minat belajar yang rendah, 80,76% yang lain mempunyai minat belajar sedang, dan 7,7% lainnya memiliki minat belajar yang tinggi.